Masks for sports: Development project of protective respiratory masks for icehockey teams during the COVID-19 pandemic - Dressler, T.; Stoff, J.; Di Pietro, T.; Cavadini, G. B.; Büsser, G.; Büsser, X.; Rüegg, C.; Müller, G.; Fox, S. (ETH Zürich, 2020)
High infection numbers but also a massive uncertainty because of the COVID-19 pandemic put high pressure on the healthcare sector and led to severe restrictions in daily life. In order to support societal and medical needs, the voluntary HelpfulETH initiative supported the healthcare sector with solutions. HelpfulETH provided and coordinated technological development also by managerial assistance. The chosen project portfolio also comprised the sports industry, as a cornerstone of societal expression and enjoy. The hereby reported project concentrated on finding a solution to counter the massive impact of COVID-19 infection in ice hockey.With the government introducing distance and hygiene regulations to reduce infection numbers, ice hockey competition was suspended and training interrupted,at the beginning of the pandemic early on. Countering the pressure and the uncertainty created by the immediate lock-down in the sport, this project pursued a fast-track development of a protective respiratory mask tailored to ice hockey. The project defined the requirements of protective gear gathering the information from athletes but also experts in the sport, in medicine and in virology. As project results, commercially available respiratory masks were not found suitable for sports, hindering the breathability and performance of the athletes. In search of a solution to meet the complex and very exigent needs, an anesthetic mask combining existent components such as a viral filter showed better suitability. Testing a realized prototype, further research and design needs were identified to allow respiration in this professional and demanding sport. A continuation of the development in regards of a possible second infection wave or future pandemic following a regular product development procedure, could build on the project results and the identified needs to consider a solution favoring active air support or further reducing the air resistance of the filters by reducing the viral protection.